Recent Advances in Computational Optimization : Results of the Workshop on 'Computational Optimization' and 'Numerical Search and Optimization' 2018 /: Results of the Workshop on 'Computational Optimization' and 'Numerical Search and Optimization' 2018. (2019) - Unknown
No abstract available